Vitamin C in Health and Disease - Anitra C. Carr (Ed.); Jens Lykkesfeldt (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Vitamin C is a pivotal water soluble electron donor in nature and an essential nutrient in man. Despite its many years as a research focus, new and increasingly regulatory functions of vitamin C in human health are continually being unravelled. This improved mechanistic insight is starting to provide rationales explaining the extensive epidemiological literature that, for decades, has consistently shown strong associations between poor vitamin C status and increased morbidity and mortality. In this Special Issue, we include original research and literature reviews by experts in the field outlining the roles of vitamin C in early, daily and late life, as well as the roles of deficiency in cardiovascular disease, inflammation and cancer.